Heterodisomy in the GNAS locus is also a cause of pseudohypoparathyroidism type 1B (iPPSD3) - Manero-Azua, Africa; Vado, Yerai; Gonzàlez Morlà, Judith; Mogas, Eduard; Pereda, Arrate; Perez de Nanclares, Guiomar (Frontiers in Endocrinology, 2024)
Objective: To identify the genetic cause underlying the methylation defect in a patient with clinical suspicion of PHP1B/iPPSD3.Imprinting is an epigenetic mechanism that allows the regulation of gene expression. GNAS locus is one of the loci within the genome that is imprinted. When the methylation pattern is affected, it causes pseudohypoparathyroidism type 1B (PHP1B) or inactivating PTH/PTHrP signaling disorder 3 (iPPSD3). Paternal uniparental isodisomy (iUPDpat) of the chromosomal region comprising GNAS locus has been described as one of the possible underlying genetic causes of the methylation alteration.We present the case of a patient clinically diagnosed with iPPSD3. We performed commercial MS-MLPA, SNP array and microsatellite study. In addition, we designed a custom MS-MLPA to analyze GNAS and nearby DMRs.Results: Methylation defect at the four GNAS-DMRs was detected, confirming the clinical diagnosis. Complementary techniques revealed the presence of a mixed isodisomy and heterodisomy of chromosome 20. Surprisingly GNAS locus is located on the heterodisomic zone.Conclusions: Paternal heterodisomy at GNAS locus is also a genetic defect associated with iPPSD3. In absence of parental samples, our custom MS-MLPA allows detecting methylation defect at GNAS locus and flanking DMRs, suggestive of UPD. We also suggest to update actual guidelines to include hUPD at GNAS locus as a cause of iPPSD3.